Relationship between Musculoskeletal Disorders and Quality of Life in Employees of Selected Hospitals in Golestan Province - Shahnaz Tabatabaei; Reza Khani Jazani; Amir Kavousi Dolanghar; maryam Azhdardor (Mazandaran University of Medical Sciences, 2017)
Introduction and purpose: In this study, we attempted to investigate the relationship between musculoskeletal disorders and quality of life in staff of selected hospitals in Golestan Province, Iran. Methods: In this descriptive-analytic study, the study population included all the employees (n=770) of Kordkuy Heart Hospital and Khatam al-Anbia Hospital of Gonbad Kavus, Golestan Province, Iran. The standard sample size was estimated at 256 based on Morgan Table. Considering the probability of subject attrition and to bolster the validity of the study, 300 employees (150 Kurdkuy and 150 Gonbad Kavus) from different occupational groups were randomly selected by stratified sampling. To collect the data, a demographic information form, the Nordic Musculoskeletal Questionnaire, and the Lancashire quality of life profile were used. Independent t-test was run in SPSS, version 22. Results: During the past year, the neck and knee were the most problematic areas, and the elbows and thighs caused the least amount of pain or discomfort among the employees. There was a significant difference between different dimensions of quality of life with consideration of musculoskeletal disorders in different areas of the body. Musculoskeletal disorders in various areas significantly diminished different aspects of quality of life. In the physical aspect of quality of life, the employees suffering from musculoskeletal disorders in all areas were significantly different from those without any problems. Conclusion: According to the results of this study, musculoskeletal disorders are one of the workplace damages that affect employees’ quality of life. Indeed, in addition to high costs, it undermines physical, mental, and social health, hence low productivity of employees.